2023
DOI: 10.1007/s12633-023-02497-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silica Nanoparticles and Modified Silica Nanoparticles on the Mechanical and Swelling Properties of EPDM/SBR Blend Nanocomposites

Abstract: The in uences of nanosilica and modi ed nanosilica on cure, compression set, mechanical and swelling characteristics are studied in blends of ethylenepropylene-diene monomer (EPDM)/styrene-butadiene rubber (SBR). In EPDM/SBR composites, the nanosilica made from rice husk ash (RHA) was utilised as a reinforcing nano ller. The interaction between the nanosilica and the EPDM/SBR matrix at the interface is crucial for the production of rubber composites. This study uses bis [3-(triethoxysilyl)propyl] tetrasul de (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The tensile properties and tear strength obtained from this study showed comparable results to the previous studies on the sulfur‐vulcanized EPDM‐silica composites. [ 26,49 ] Furthermore, The SiEPDM‐silica composites in this study displayed higher tensile properties and tear strength than the previous works regarding to the sulfur‐free cross‐linked EPDM‐silica composites with the same loading level of fillers. [ 15,50 ]…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…The tensile properties and tear strength obtained from this study showed comparable results to the previous studies on the sulfur‐vulcanized EPDM‐silica composites. [ 26,49 ] Furthermore, The SiEPDM‐silica composites in this study displayed higher tensile properties and tear strength than the previous works regarding to the sulfur‐free cross‐linked EPDM‐silica composites with the same loading level of fillers. [ 15,50 ]…”
Section: Resultsmentioning
confidence: 61%
“…For the SiEPDM10silica sample, crazing river lines were evidenced crosslinking and some of the crazes are stopped by the silica particles (Figure 7B), indicating the effective reinforcement and improved compatibility. [26,51] Furthermore, the silica particles within EPDM10silica composites showed clear border with the rubber matrix (Figure 7D), while within the SiEPDM10silica there were interface bonding between the fillers and matrix (Figure 7E). There are visible signs of interpenetrating EPDM chains among the silica particles that led to improved compatibility and the silica particles were fully infiltrated when the silane modified EPDM was employed.…”
Section: Fracture Morphologymentioning
confidence: 97%
See 1 more Smart Citation
“…Figures 14(b) and (c) at room temperature also depict the effects of molar mass/molecular weight on aliphatic and chlorinated penetrants on the MPU by silicone rubber/mHNTs nanotubes. Prior studies [82] have shown that solvent absorption decreases with increasing molar mass/molecular weight of both aliphatic and aromatic penetrants. Dichloromethane in particular demonstrates lower equilibrium absorption than n-pentane in aliphatic solvents and lower equilibrium intake than chloroform in chlorinated solvents.…”
Section: Figure 10 Abrasion Loss Of Silicone Rubber Nanocompositesmentioning
confidence: 92%
“…Figure11(b & c) demonstrates the impact of the molar mass/molecular weight of aliphatic and chlorinated penetrants on the MPU by PVMQ/HNTs at room temperature, respectively. It is observed that solvent absorption decreases as the molar mass/molecular weight of aliphatic and aromatic penetrants increases[57]. Speci cally, n-octane has lower equilibrium absorption than n-pentane among aliphatic solvents, and dichloromethane exhibits less equilibrium uptake than chloroform in chlorinated solvents[58][59].…”
mentioning
confidence: 99%